Development of 2A-CHYSEL technology based multicistronic expression systems for imparting fungal tolerance: Development of 2A-CHYSEL technology based multicistronic expression systems for imparting fungal tolerance - KONDA ARAVIND KUMAR,; P B KIRTI,; V DINESH KUMAR, (Journal of Oilseeds Research, 2020)
Multigene transfer is an approach for development of transgenic crops simultaneously expressing many genes. With an aim to impart necrotrophic fungal tolerance through transgenic approach, the present study describes the development of multigene construct bearing three antifungal genes as a single transcriptional unit capable of expressing at high levels and evading transgene silencing.